A retrospective observational study of EEG findings and antiepileptic drug use among children referred for EEG to Zambia's University Teaching Hospital. Issue 4 (16th October 2018) - Ciccone, Ornella; Chabala, Chishala; Tembo, Owen; Mathew, Manoj; Grollnek, Alice K.; Patel, Archana A.; Birbeck, Gretchen L.
Summary: Objective: Despite the heavy burden of epilepsy in Sub‐Saharan Africa, there remains a relative paucity of neurophysiology services and limited published data on electroencephalography (EEG) features among African children. The aim of this study was to describe clinical characteristics, EEG findings, and antiepileptic drug (AED) use among children referred for EEG to the University Teaching Hospital in Zambia. Methods: EEG referrals and reports from 2013–2015 were reviewed. Within the context of routine care, EEG studies were interpreted by readers with advanced training in child neurology and clinical neurophysiology. Clinical data provided in the referral including seizure semiology and EEG findings were systematically extracted and analyzed. Results: A total of 1, 217 EEG reports were reviewed, with 1, 187 included in the analysis. Median age was 7 years (interquartile range [IQR] 3–11) and 57% were male. Seventy‐three percent of 554 had documented seizure onset before 5 years of age. Among the 23% with seizure etiology documented, 78% were associated with perinatal injuries and central nervous system (CNS) infections. EEG abnormalities were found in 75% of the studies. Clinical semiology per referral identified focal seizures in 29%, but EEG findings increased this proportion to 63% (p = 0.004). Sixty‐two percent were taking AEDs, with 85% on monotherapy. The most commonly used AED was carbamazepine (49%).There was no association between the choice of AED and clinical semiology (all p's > 0.05). Significance: This tertiary care center study identified >60% of referred children to have localization‐related epilepsies, with at least 18% of epilepsies being from potentially preventable causes. These findings are consistent with multi‐country, population‐based data from elsewhere in Africa. Seizure semiology assessed in routine, nonspecialist care does not predict AED choice, and the presence of focality is underestimated in routine care.